Review on the innovations and challenges in developing rapid colorimetry and turbidity NPK soil test kits for commercial soil nutrient analysis - Teh, Christopher Boon Sung; Tan, Ngai Paing; Lok, Melissa Mei Teng; Tee, Yei Kheng (Universiti Putra Malaysia, 2024)
This study reviews the progress and challenges in developing rapid colorimetric and turbidimetric test kits for commercial soil nutrient analyses, focusing on nitrogen, phosphorus, and potassium. Although common laboratory analytical techniques are accurate, they are often expensive and require advanced technical skills. Consequently, commercial in situ soil test kits have gained attention as potential alternatives to these tests. These kits use universal extractants that can simultaneously extract multiple nutrients and colorimetry and turbidimetry for nutrient determination. A critical aspect of these kits is the selection of suitable extractants that are effective under various soil conditions, chemically safe, compatible with analytical systems, and have a long shelf life. This review assesses the efficacy of several extractants in conjunction with colorimetric and turbidimetric reagents. Examples include H3A-4 and Kelowna extractants using the zinc–Griess reagent, salicylic method, molybdenum yellow method, and sodium tetraphenyl boron method for nitrate, ammonium, phosphorus, and potassium, respectively. These extractants and reagents have been highlighted for their adaptability, safety, rapid color formation, and minimal compatibility issues, making them promising candidates for rapid test kit development. However, rapid soil test kits are designed to provide a general understanding of soil nutrient status. They are not intended to replace detailed laboratory analyses in situations where precision is critical. Additionally, these kits should be validated against standard laboratory methods to determine their accuracy and reliability. This review highlights the importance of balancing practicality and accuracy when developing rapid soil test kits for soil nutrient analysis.